2017
DOI: 10.1007/s00431-017-2904-1
|View full text |Cite
|
Sign up to set email alerts
|

Dutch national immunization schedule: compliance and associated characteristics for the primary series

Abstract: Delayed vaccination during the primary vaccination schedule occurs in one sixth of the Dutch children. Efforts to improve compliance should be focused in particular on preterm infants, infants with low birth weight and infants whose parents are not born in the Netherlands. What is Known: • A delayed start of vaccination leads to a longer period at risk for infectious diseases, e.g. pertussis • Delayed vaccination is associated with several factors including prematurity, low birth weight, family size, birth ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This can be partly explained by having received a prior dose later than scheduled but the subsequent dose at the scheduled age. Our findings confirm previous studies with smaller study populations that also reported high timeliness, up to 95%, of first vaccine doses scheduled in the first year of life, with a decreasing trend for subsequent doses and vaccines given after the age of 1, and proportions between 22% and 87% of children with at least one delayed vaccination compared to 80% in our study [5] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [31] , [32] , [33] , [34] .…”
Section: Discussionsupporting
confidence: 92%
“…This can be partly explained by having received a prior dose later than scheduled but the subsequent dose at the scheduled age. Our findings confirm previous studies with smaller study populations that also reported high timeliness, up to 95%, of first vaccine doses scheduled in the first year of life, with a decreasing trend for subsequent doses and vaccines given after the age of 1, and proportions between 22% and 87% of children with at least one delayed vaccination compared to 80% in our study [5] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [31] , [32] , [33] , [34] .…”
Section: Discussionsupporting
confidence: 92%
“…These countries instead recommend the first dose of the hepatitis B vaccine to be given during the first six to nine weeks of life to all infants, including preterm infants, as part of the routine hepatitis B vaccination series. These countries are Germany [ 16 ], Ireland [ 20 , 21 ], the Netherlands [ 25 , 26 ], New Zealand [ 27 ], and the United Kingdom (UK) [ 30 ]. The country with the earliest hepatitis B vaccination of these five is New Zealand, which recommends the first dose at six weeks of age for all infants, including medically stable preterm infants [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The country with the earliest hepatitis B vaccination of these five is New Zealand, which recommends the first dose at six weeks of age for all infants, including medically stable preterm infants [ 27 ]. Dutch guidelines recommend practitioners to provide the first dose between six to nine weeks of age [ 25 , 26 ], whilst guidelines from Germany, Ireland and the UK state that all infants should receive their first dose of the hepatitis B vaccine at the age of two months [ 16 , 20 , 21 ] or eight weeks [ 30 ]. Of note, each of these countries recommend the first dose of the hepatitis B vaccine to be provided as part of a hexavalent combination vaccine (DTaP-IPV-Hib-HepB), providing protection against diphtheria, tetanus, pertussis, poliomyelitis, Haemophilus influenzae type b and hepatitis B [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This nationwide study sought to evaluate the impact of introducing the DTaP-IPV/Hib vaccine into NIP on infant vaccination practice. In total, 96.7% of infants born between 2013 and 2019 completed primary vaccination series of D-I-H by 12 months of age, exhibiting a higher coverage rate than global averages [14] , [15] , [16] , [17] . There was a steady increase in the rate over the birth years (from 95.1% in 2013 to 97.8% in 2019).…”
Section: Discussionmentioning
confidence: 99%